Atherogenic Index in Type 2 Diabetes and Its Relationship with Chronic Microvascular Complications - Zhen Li; Qi Huang; Li Sun; Tengfei Bao; Zhe Dai (International Journal of Endocrinology)
Objective. This study was designed to investigate risk factors related to atherogenic index of plasma (AIP), as well as the relationship between AIP and chronic microvascular complications in patients with type 2 diabetes (T2DM). Methods. This study included 2523 patients with T2DM who had not been treated with lipid-lowering drugs and were admitted to the Department of Endocrinology at Zhongnan Hospital, Wuhan University, during the period from January 2015 to February 2018. Anthropometric indicators were measured after overnight fasting. Low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglyceride (TG) were detected by enzymatic analysis. Standard 75 g oral glucose tolerance testing was performed to measure 0 and 2 hr plasma levels of glucose and insulin. Insulin sensitivity was assessed with HOMA-IR. Results. Increase in AIP was associated with an increased risk for hypertension (P<0.05), HbA1c (P<0.05), HOMA-IR (P<0.05), UA (P<0.05), and decreased eGFR levels (P<0.05). Furthermore, AIP values directly correlated with BMI (r=0.182, P<0.001), waist circumference (r=0.129, P<0.001), blood glucose index (FBG (r=0.153, P<0.001), PPBG (r=0.117, P<0.001), and HbA1c (r=0.074, P<0.001)), insulin resistance (HOMA-IR; r=0.112, P<0.001), and uric acid (UA, r=0.177, P<0.001). Multiple logistic regression analysis showed that waist circumference, HOMA-IR, FBG, systolic blood pressure, and UA were independent risk factors for AIP (all P<0.05). The prevalence of diabetic neuropathy and metabolic syndrome was significantly higher among patients with higher AIP. Conclusion. AIP represents a clinically convenient indicator for the detection of T2DM with high risk of complications and associated diseases and thus is a good predictor and indicator for follow-up monitoring in the treatment of patients with high-risk type 2 diabetes.